The Brain Drain of Egyptian Physicians and Its Driving Factors: A Cross-Sectional Study - Hebatalla Ahmed Ismail; Sungsoo Chun (Social Sciences)
Background: During the past years, brain drain has become an international problem. A shortage of human resources in the medical field revealed its challenges during the COVID-19 pandemic. Despite the large number of medical school graduates in Egypt, the reports of the World Health Organization and the Egyptian Medical Syndicate indicate a yearly decline in the number of physicians in Egypt. The aim of this study is to determine the factors affecting Egyptian physicians’ intention to leave Egypt to work in another country. Methods: This is a cross-sectional study with a self-administered questionnaire via the snowball sampling technique that focused on Egyptian physicians who graduated from Egyptian universities and were working in Egypt. The outcome measures include the migration intentions of physicians and their satisfaction with different aspects of work, their family and housing conditions, and their demographic characteristics. Results: The questionnaire was answered by 249 Egyptian physicians, 140 of whom were living in Egypt. The findings revealed that 66.4% of the sample in Egypt were considering working abroad. Work satisfaction was the main factor affecting the decisions of physicians in Egypt; the physicians with a lower satisfaction score were 20 times more likely to leave their country. Additionally, physicians who classified themselves as having a low economic status, being younger, or who were male were more likely to leave. Conclusion: Egypt may suffer major resource losses as a result of the high degree of dissatisfaction among physicians regarding their working conditions. To realize Egypt’s Vision 2030 for health and economic progress, policymakers need to address the driving factors and take probable intervention measures to reduce the drain of our physicians.